HYPERPHAGIA REACTIONS WITHIN EATING DISORDERS. CLINICAL FEATURES AND THERAPY - O. A. Gladyshev (Столичная издательская компания, 2015)
Aim. To evaluate clinical features of hyperphagia reactions, their significance in attraction abnormities within eating disorders and treatment options for these conditions with escitalopram.Material and methods. Mental state of 39 women (age 19-50 years) with psychogenic overeating and obesity (body mass index of 30 to 53 kg/m2) was studied. Patients were admitted to the Institute of Nutrition of the Russian Academy of Medical Sciences. Diagnostic criteria for International Classification of Diseases, 10th edition, as well as Eating Disorder Inventory (EDI), Hospital Anxiety and Depression Scale (HADS) and Ferreri Anxiety Rating Diagram (FARD) were used for syndrome qualifications. Patient Global Impression of Change was also studied using a 4-point scale of results (excellent, good, fair, and negative).Results. Clinical features of hyperphagic reactions were found. Escitalopram treatment course was completed with excellent and good results in 80% of patients. 50%-reduction in HADS score for anxiety was found in 74% of patients, for depression - in 63%, and for Ferreri scale - in 68% of patients. Escitalopram promoted more intensive body weight loss: 11% vs 8% of baseline weight in active and control groups, respectively. Adverse events occurred only in 7 (36%) patients; they were transient and did not require therapy discontinuation.Conclusion: Significant differences of premanifest disorders were often observed in patients history. Escitalopram in these patients showed efficacy in improvement of both mental and somatic symptoms of anxiety. It decreased dependence on food as a factor mitigating affect and stress, thus provided better results in body weight reduction.